New records of diatoms for the algal flora of Ukraine from water bodies of Nyzhniosulsky National Nature Park - Kryvosheia, O.M.; Kapustin, D.O. (Український ботанічний журнал, 2019)
Here we present new records of diatoms for the algal flora of Ukraine from water bodies of Nyzhnosulsky National Nature Park. The following species are recorded for the first time in Ukraine: Achnanthidium eutrophilum, Caloneis biconstrictoides, Encyonema lacustre, Gomphonema angusticephalum, Karayevia kolbei, K. suchlandtii, Placoneis abiskoensis, P. paraelginensis, Stauroneis balatonis, and Tryblionella salinarum. Some of them are rare and noteworthy taxa. For Caloneis biconstrictoides, it is the third known record in the world; Placoneis abiskoensis is a rare Holarctic species. The reported records of the new, rare and interesting taxa in the investigated water bodies may indicate a high nature conservation significance of Nyzhniosulsky National Nature Park as an algal reserve. The taxonomic position, synonymy, morphological features, information about ecology, distribution and original photomicrographs are provided. У статті представлені дані щодо нових та цікавих видів діатомових водоростей флори України з водойм Національного природного парку "Нижньосульський". Види Achnanthidium eutrophilum, Caloneis biconstrictoides, Encyonema lacustre, Gomphonema angusticephalum, Karayevia kolbei, K. suchlandtii, Placoneis abiskoensis, P. paraelginensis, Stauroneis balatonis, Tryblionella salinarum є новими знахідками для флори України. Серед них є рідкісні та цікаві таксони. Для Caloneis biconstrictoides це третє місцезнаходження у світі, Placoneis abiskoensis є рідкісним голарктичним видом. Наявність нових, рідкісних та цікавих таксонів у досліджених водоймах засвідчує високе значення Національного природного парку "Нижньосульський" як альгорезервату зазначених видів. У статті наведено відомості про систематичне положення, синоніми, морфологічні характеристики, екологію і поширення виявлених видів та їхні оригінальні мікрофотографії.